SATISFACTION OF HEALTH EMPLOYEES AT ANDROLOGY AND FERTILITY HOSPITAL OF HANOI IN 2022 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: To assess the satisfaction of medical staff at Andrology And Fertility Hospital Of Hanoiand some related factors.Methods: A descriptive cross-sectional study with analysis.Results: The overall satisfaction score of medical staff with the job is 3.58 ± 0.47 points. The overallsatisfaction rate of medical staff is 56.2%. Factors related to the overall satisfaction of medical staff:Medical staff in the group with undergraduate and postgraduate training have a satisfaction rate 3.31times higher than that of the group with training qualifications. In mid-level training, medical staffin the clinical sector had a satisfaction rate 2.48 times higher than that of the administrative group.Medical staff in the subclinical sector have a satisfaction rate 2.44 times higher than that of medicalstaff in the administrative division. The overall satisfaction rate of medical staff with working timeof more than 5 years is 3.31 times higher than that of medical staff with working time from 6 monthsto 1 year.Conclusion: The overall satisfaction rate of medical staff is 56.2%, the overall satisfaction score is3.58 ± 0.47 points. Factors related to general satisfaction include professional qualifications, work,and working time. Therefore, the hospital needs a support mechanism to increase the income ofmedical staff, organizes recruitment examinations to ensure regimes and policies for medical staffworking at the hospital, and develop a plan, training support plan for medical staff working in thedepartment.
Keywords: Hospital, satisfaction, medical staff.